A robust adhesion between extruded polystyrene foam and mortar through different chemical linkages under ultraviolet-ozone irradiation. (22nd August 2022) - Jin, Xiaodong; Wu, Xinyi; Cui, Suping; Wang, Wanfu; Zhang, Yao; Sun, Shibing; Sun, Dawei
Highlights: Effective modification of extruded polystyrene foam (XPSF) by the ultraviolet-ozone. Amphipathic silane coupling agents as the adhesion promoters between XPSF and mortar. A significant improvement on the interfacial strength of XPSF/mortar. The chemical linkages can be induced by different kinds of silanes. Abstract: The inert surface of extruded polystyrene foam (XPSF) was activated by the ultraviolet-ozone (UVO) irradiation, followed by the surface coupling reactions with γ-mercaptopropyl trimethoxysilane (MPTMS) and vinyl triethylsilane (VTEO) to improve the interfacial affinity between the organic XPSF and inorganic mortar. The reaction conditions (including reaction time, concentration and pH of the silanes) were thoroughly investigated in order to reach the maximum bonding strength (BS) of XPSF/mortar composites. It was suggested that the presence of MPTMS could increase the BS value from 0.04 MPa to 0.178 MPa (reaction time: 10 min, concentration of MPTMS: 2% and pH value of the silane solution: 4). For VTEO, the maximum BS value reached to 0.140 MPa (activation and reaction time: 7 and 3 min, concentration of VTEO: 5% and pH value of the silane solution: 7). According to the mechanism analysis, the thiol groups in MPTMS have the strongest reactivity with activated XPSF surface after UVO exposure, leading to the maximized interfacial strength between the organic insulation materials and inorganic mortar.